Constitutive heterochromatin and the structural complexity of chromosomes in columbiformes and psittaciformes (AVES) - de Lucca, Edmundo José [UNESP] (Firenze University Press, 1983)
Studies on the correlations between the length of the pericentromeric heterochromatin block and the internal structural complexity of chromosomes showed significance for some chromosomes both in Psittaciformes and Columbiformes. In Columbiformes, internal rearrangements resulting in translocation of portion of pericentromeric heterochromatin to interstitial chromosome regions seem to have occurred in the interspecific homologous chromosomes for which negative regression was obtained. In Psittaciformes, it is possible that in the homologues for which positive regression was obtained, part of the heterochromatin that was added by fusion and translocation processes from microchromosomes and macrochromosomes may have been transferred to the pericentromeric region. © 1983 Taylor & Francis Group, LLC.